OVERVIEWOF THE STATUS OF HEAVYMETALACCUMULATION BY HELMINTHS WITH A NOTE ON THE USE OF IN VITRO CULTURE OF ADULTACANTHOCEPHALANS TO STUDY THE MECHANISMS OF BIOACCUMULATION - de Buron, Isaure (2009)
Bioaccumulation of metals by helminths is a well acknowledged phenomenon that has triggered increasing research interest in the past two decades and found applications in environmental studies. The ecological literature is fairly abundant but still shows gaps with some taxa not having been studied. Variations in the ability of helminths to sequester various metals are recognized and a synthetic overview of the literature is provided herein. Adult acanthocephalans are known to be particularly efficient as bioaccumulators of heavy metals. We optimized an in vitro culture technique of the acanthocephalan Moniliformis moniliformis and initiated in vitro exposure to cadmium and lead. We propose to use this technique to study the mechanisms of uptake and sequestration of heavy metals, which are yet to be understood.